Plasma protein changes reflect colorectal cancer development and associated inflammation - Urbiola-Salvador, Víctor; Jabłońska, Agnieszka; Miroszewska, Dominika; Huang, Qianru; Duzowska, Katarzyna; Drężek-Chyła, Kinga; Zdrenka, Marek; Śrutek, Ewa; Szylberg, Łukasz; Jankowski, Michał; Bała, Dariusz; Zegarski, Wojciech; et al. (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is the third most common malignancy and the second leading cause of death worldwide. Efficient non-invasive blood-based biomarkers for CRC early detection and prognosis are urgently needed. To identify novel potential plasma biomarkers, we applied a proximity extension assay (PEA), an antibody-based proteomics strategy to quantify the abundance of plasma proteins in CRC development and cancer-associated inflammation from few µL of plasma sample. Among the 690 quantified proteins, levels of 202 plasma proteins were significantly changed in CRC patients compared to age-and-sex-matched healthy subjects. We identified novel protein changes involved in Th17 activity, oncogenic pathways, and cancer-related inflammation with potential implications in the CRC diagnosis. Moreover, the interferon γ (IFNG), interleukin (IL) 32, and IL17C were identified as associated with the early stages of CRC, whereas lysophosphatidic acid phosphatase type 6 (ACP6), Fms-related tyrosine kinase 4 (FLT4), and MANSC domain-containing protein 1 (MANSC1) were correlated with the late-stages of CRC. Our study identifies novel plasma protein signatures associated with CRC development and suggests that IFNG, IL32, IL17C, ACP6, FLT4, and MANSC1 could be used as potential plasma biomarkers in CRC.